Pengaruh Brand Equity, Kreativitas Iklan, Kepuasan Konsumen, Terhadap Keputusan Pembelian Online Di Shopee (Studi Kasus Mahasiswa FEB UNISMA Angkatan Tahun 2019) - Nanda Anisa Rizki; Nurhidayah Nurhidayah; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of Brand Equity, Advertising Creativity, Consumer Satisfaction, on Online Purchasing Decisions at Shopee in Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019. With an active sample used in this study, 90 active students of the Faculty of Economics and Business Islamic University of Malang class of 2019. The analytical method used in this research is quantitative data analysis using multiple linear regression analysis. The results of this study indicate that brand equity has no effect on purchasing decisions at Shopee. Advertising creativity has no effect on purchasing decisions at Shopee. Consumer satisfaction influences purchasing decisions at Shopee. Keywords: Brand Equity, Advertising Creativity, Consumer Satisfaction And Purchasing Decisions